India's balance of indebtedness, 1898-1913 - Pandit, Y. S. , 1910- (London : George Allen and Unwin, 1937)
Study of the composition of India's foreign trade with reference to the country's balance of payments position
Master microform held by: ICRL
Includes bibliographical references and index
Keywords: Balance of payments -- India; Balance of trade -- India; India -- Commercial policy